Digital System Failure, Moral Reasoning, and Voluntary Tax Compliance : Evidence from Indonesia’s Coretax Implementation - Martinus Sony Erstiawan; Nia Yuniarsih; Yuli Yanti Wulandari; Tony Soebijono; Mita Otik Wiraswati (JAS (Jurnal Akuntansi Syariah), 2026)
The digitalisation of tax administration has become a central fiscal reform strategy worldwide; however, technological implementation frequently fails to align with taxpayer expectations, creating a gap between institutional intent and user experience. Purpose – This study aims to examine how digital system failures are interpreted by taxpayers and how such experiences shape perceptions of justice, moral reasoning, and voluntary compliance towards the tax authority. Method – The research employed a qualitative narrative inquiry design, analysing 236 digital narratives collected from public platforms and conducting semi-structured interviews with 18 purposively selected taxpayers who had experienced system disruptions. Data were examined using thematic analysis and qualitative content analysis, supported by NVivo, to identify recurring patterns of technological acceptance and resistance. Findings – The results demonstrate that technical failures and procedural complexities (accountable for 65.3% of reported issues) created a misfit between task requirements and system capabilities, leading to negative expectation confirmation. These experiences evolved beyond mere technical inconvenience into emotional frustration and perceptions of procedural injustice, ultimately weakening institutional legitimacy and shifting compliance from voluntary willingness to enforced obligation. Implications – The study contributes theoretically by integrating behavioural and ethical perspectives to explain technology acceptance during system failure. Practically, it highlights that successful digital tax reform requires operational reliability, procedural clarity, and the preservation of moral legitimacy, rather than mere technological modernisation.